Ab initio study of tungsten defects near the surface. (24th March 2016) - Guerrero, C L; Gordillo, N; Iglesias, R; Perlado, J M; Gonzalez, C
Abstract: A first principles analysis of the behaviour of point defects, namely, self-interstitial atoms, a single vacancy and light impurity atoms such as H and He in tungsten is reported. These defects can be produced in the first wall of the future nuclear fusion reactors due to the high radiation fluxes present. The evolution of defects that appear in the bulk and end up reaching the surface has been followed. An energetic study has been combined with a detailed charge density analysis of the system by means of the SIESTA code. The resulting data have been validated by confronting them with those obtained with a more precise plane wave code, namely VASP. Meanwhile, the structural and the mechanical properties of the system have been positively compared with experimental measurements. Such comparisons have led us to present a new SIESTA basis for tungsten. This complete analysis establishes a nanoscopic view of the phenomena involving the presence of light atoms at native defects in tungsten, paying special attention to the vicinity of surfaces.